Clinical implications of vascular dysfunction in acute and convalescent COVID‐19: A systematic review. (1st September 2022) - Mavraganis, Georgios; Dimopoulou, Maria‐Angeliki; Delialis, Dimitrios; Bampatsias, Dimitrios; Patras, Raphael; Sianis, Alexandros; Maneta, Eleni; Stamatelopoulos, Kimon; Georgiopoulos, Georgios
Abstract: Background: Accumulating evidence suggests that endothelial dysfunction is implicated in the pathogenesis and severity of coronavirus disease 2019 (COVID‐19). In this context, vascular impairment in COVID‐19 might be associated with clinical manifestations and could refine risk stratification in these patients. Methods: This systematic review aims to synthesize current evidence on the frequency and the prognostic value of vascular dysfunction during acute and post‐recovery COVID‐19. After systematically searching the MEDLINE, clinicaltrials.gov and the Cochrane Library from 1 December 2019 until 05 March 2022, we identified 24 eligible studies with laboratory confirmed COVID‐19 and a thorough examination of vascular function. Flow‐mediated dilation (FMD) was assessed in 5 and 12 studies in acute and post‐recovery phase respectively; pulse wave velocity (PWV) was the marker of interest in three studies in the acute and four studies in the post‐recovery phase. Results: All studies except for one in the acute and in the post‐recovery phase showed positive association between vascular dysfunction and COVID‐19 infection. Endothelial dysfunction in two studies and increased arterial stiffness in three studies were related to inferior survival in COVID‐19. Discussion: Overall, a detrimental effect of COVID‐19 on markers of endothelial function and arterial stiffness that could persist even for months after the resolution of the infection and provide prognostic value was congruent across published studies. Further research is warranted to elucidate clinical implications of this association. Abstract :